CAPOEIRA E ENSINO DA CULTURA AFRO-BRASILEIRA: ANÁLISE DO MATERIAL DO ALUNO - CICLO II - Irís de França Britto; Wagner Aparecido Caetano; Arilda Inês Miranda Ribeiro (Universidade do Oeste Paulista, 2014)
This study aimed to prepare an analysis on the reality of the teaching of African culture in schools within the curriculum of the Elementary School, building an understanding of the importance of Law 10.639/2003 ( African - Brazilian theme ) for the Brazilian education and discussing the possibility of applying via the Physical Education classes , embodied in the teaching of capoeira. The methodology was based on the Qualitative Approach by developing a bibliogaphic resarch and analysis of the teaching material of elementary education - Cycle II of the State of São Paulo . We concluded that capoeira is embedded in the curriculum of primary education cycle - II in 8th grade / 9 th , but its practice still does not cover all necessary aspects for an effective law.